2020
DOI: 10.1099/ijsem.0.004495
|View full text |Cite
|
Sign up to set email alerts
|

Lichenicola cladoniae gen. nov., sp. nov., a member of the family Acetobacteraceae isolated from an Antarctic lichen

Abstract: Two Gram-stain-negative, facultative anaerobic, chemoheterotrophic, pink-coloured, rod-shaped and non-motile bacterial strains, PAMC 26568 and PAMC 26569T, were isolated from an Antarctic lichen. Phylogenetic analysis based on 16S rRNA gene sequences revealed that strains PAMC 26568 and PAMC 26569T belong to the family Acetobacteraceae and the most closely related species are G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Novel is also the finding of a complete set of CBB genes in the family Acetobacteraceae (order Acetobacterales , class Alphaproteobacteria ). It has been previously reported that organisms in this family encode most of the enzymes required for the CBB, but no genetic evidence for a phosporibulokinase (PRK) was found ( 47 ). In contrast, we detected in MAG 3300005985_13 of this family a protein sequence for PRK I with a sequence similarity of 69.4% to the reference PRK I from Cereibacter sphaeroides .…”
Section: Resultsmentioning
confidence: 99%
“…Novel is also the finding of a complete set of CBB genes in the family Acetobacteraceae (order Acetobacterales , class Alphaproteobacteria ). It has been previously reported that organisms in this family encode most of the enzymes required for the CBB, but no genetic evidence for a phosporibulokinase (PRK) was found ( 47 ). In contrast, we detected in MAG 3300005985_13 of this family a protein sequence for PRK I with a sequence similarity of 69.4% to the reference PRK I from Cereibacter sphaeroides .…”
Section: Resultsmentioning
confidence: 99%
“…Although Lichenihabitans minor tends to be associated with lichens, our detection of this species is not surprising, given the prevalence of lichens in the habitat of boreal mosses [75]. Lichenicola and Lichenicoccus , eponymously, are taxa that are associated with lichens, for example Lichenicola cladoniae has previously been found in Antarctic lichens [76]. Overall, through our analysis, we observed enrichments in several genera such as CAHJXF01 , CAHJXG01 , Methylobacteria , Lichenihabitans , and RH-AL1 spp.…”
Section: Resultsmentioning
confidence: 87%
“…[3] from a hot spring, which was taxonomically included in the family Acetobateraceae , order Rhodospirillales . Members of this family were discovered and isolated from various habitats, such as acidic mine drainage [4], acidic northern wetlands [5], sediment of shallow stream [6], Antarctic lichen [7], hot springs [8] and so on. At the time of writing, only one species, Caldovatus sediminis , with a validly published name has been documented on the LPSN website (www.bacterio.net).…”
Section: Full-textmentioning
confidence: 99%